1978
DOI: 10.1192/s0007125000283268
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Schizophrenic Patients in the Community

Abstract: SummaryA sample of 190 patients, diagnosed as schizophrenic by the same psychiatrist, have been surveyed in an urban community and their clinical and social status assessed. Compared to the local population as a whole, a significantly greater proportion of the men had never married, and although the women had married at approximately the same rate as those in the general population, 25 per cent of them had been divorced by the time of the interview. Assessments of the subjects' clinical condition by the Presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1979
1979
2006
2006

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(17 citation statements)
references
References 3 publications
2
15
0
Order By: Relevance
“…The sociodemographic and psychiatric characteristics of the clients were very similar to those described in previous studies of services for people with long-term mental health problems (see Cheadle et al 1978, Beels et al 1984, Mulkern & Manderscheid 1989, Wells et al 1989, Ford et al 1993. The majority of the clients were male (66%), single (94%), unemployed (98%), and living alone (80%).…”
Section: Characteristics Of All Male and Female Clients Within Rccssupporting
confidence: 75%
“…The sociodemographic and psychiatric characteristics of the clients were very similar to those described in previous studies of services for people with long-term mental health problems (see Cheadle et al 1978, Beels et al 1984, Mulkern & Manderscheid 1989, Wells et al 1989, Ford et al 1993. The majority of the clients were male (66%), single (94%), unemployed (98%), and living alone (80%).…”
Section: Characteristics Of All Male and Female Clients Within Rccssupporting
confidence: 75%
“…On the other hand, other investigators have found that: neurotic and not psychotic symptoms in schizophrenia were associated with social handicaps [31]; patients with anxi-( ety/depressive symptoms were receiving higher doses of neuroleptics and had more extrapyramidal side-effects (EPSE) [35]; first episode patients with anxiety comorbidity had longer hospitalisations, were younger and less likely to be married [36]; patients with comorbid anxiety disorders had more severe illness in the previous month and a higher proportion lived alone [40]; and patients with comorbid GAD had a higher number of admissions compared with other anxiety comorbidities [40].…”
Section: Effect Of Anxiety Comorbidity On Outcomementioning
confidence: 90%
“…It is frequently forgotten that most psychiatric patients are subject to heightened anxiety. For example, it is now clear that one of the most disabling features of schizophrenia is not the presence of psychotic symptoms per se, but instead the persistence of chronic neurotic symptoms that result in social isolation (Cheadle, Freeman and Korer 1978). Some of the potential benefits of relaxation training are listed in table 2.…”
Section: Relaxation Training In Psychiatric Admission Unitsmentioning
confidence: 99%